Genetic and phenotypic parameters for birth and weaning weights of purebred and crossbred N'dama and West African Shorthorn cattle - Ahunu, B.K.; Arthur, P.F; Kissiedu, H.W.A. (Elsevier, 1997)
Calf records for a 30 year period (1965-1995) on purebred and crossbred N'dama and West African Shorthorn (WASH) cattle and their crosses with Santa Gertrudis or Red Poll were analyzed to determine factors affecting birth and weaning weights and to estimate genetic parameters. Male calves weighed heavier (p< 0.05) at birth and at weaning. Similarly period (year grouping) significantly influenced birth and weaning weights of calves. Season of birth did not influence calf weight at birth but significantly affected calf weaning weights. Purebred calves were similar in weight at birth and at weaning. Santa Gertrudis crossbreds weighed heavier than Red Poll crossbreds at birth only but not at weaning. Generally the poor level of nutrition of the natural pasture did not permit improved weaning weights in calves, which were heavier at birth. Additive direct heritability estimates were 0.45±0.08 for birth weight and 038±0.18 for weaning weight. Moderate genetic correlation (0.48) between birth and weaning weights indicates that selection for one trait would lead to moderate positive correlated response in the other trait. Due to negative genetic correlation (-0.29±0.16) between direct and maternal effects for weaning weight, and moderate heritabilities for both traits, selection for both the direct and maternal components of preweaning traits is advised.